Formulation and Evaluation of Polyherbal Emulgel for Treatment of Acne - Amisha Chauhan; Shikha Baghel Chauhan (Current Research in Pharmaceutical Sciences, 2022)
Skin disease is a persistent inflammatory skin disorder that affects around 70% of teenage females throughout puberty. To counteract this problem, antibiotics are being administered more often, which has resulted in a variety of undesirable side effects. As a result, as a first-line topical therapy, it must target on the herbal formulation. In this study, medicinal plant extracts and oils with high antibacterial activity, such as Curcuma longa and Aloe barbadensis, tea tree oil, and lemongrass oil, were chosen to produce a polyherbal emulgel for the treatment of acne vulgaris. Curcuma longa, Aloe barbadensis, tea tree oil, and lemongrass oil were all extracted and reported in this study. Lemongrass oil, tea tree oil, aloe Vera extract, and turmeric extract were used in various amounts in the topical gels. After being kept at room temperature for 24 hours, the gel was prepared and evaluated. As a result of the study’s findings, a prepared polyherbal emulgel containing extracts of Curcuma longa, lemon grass oil and tea tree oil at concentrations of 0.5 percent, 5 percent, 5 percent respectively, can be used to treat acne vulgaris.